From “Philosophy of History” to “Historicism” in the Studies of Antiquity and the Middle Ages in Russia: T.N. Granovskii (1813–1855) and V.G. Vasilievskii (1838–1899) - Dmitry Starostin; Elena Kuleshova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
This article is devoted to the problem of developing methods of historical research among Russian historians of the Middle Ages of the 19th century. Methods and materials. We used methods of studying historiography, developed by Russian scholars recently, as well as the ideographic method of historical inquiry. Analysis. In this article, an attempt is made to illustrate an important breakthrough in the views of Russian scholars of antiquity and the Middle Ages that occurred amid the 19th century. T.N. Granovskii and P.N. Kudriavtsev, whose formative years fell on the first half of the 19th century, started their studies of history with a belief that the knowledge of the concepts of the philosophy of history was critical for historical inquiry. But in the 1850s, T.N. Granovskii came to insist that any study of history must begin with the critical analysis, the “deconstruction” of the sources. V.G. Vasilievskii, a future scholar of Byzantium, established his studies in the 1860s on a thorough analysis of the monographs on Roman history that sought to deconstruct the myths of its early period. Results. It was shown that the philosophical and methodological divide, which started to show in the late articles of T.N. Granovskii, received a thorough development in the works of V.G. Vasilievskii, who did not consider the philosophy of history important and started his studies with the monographs that made the critique of sources and deconstruction of historical narratives the main research method, especially in the description of the epoch-making events during the creation of the Roman Empire and the time of its collapse in the West. Authors’ contributions. D.N. Starostin was responsible for the investigation of the European authors’ concepts and their comparison with those of Russian scholars, as well as for the work with archival materials. E.V. Kuleshova was responsible for analysis of the Russian historians’ views in the context of the development of Russian historical thought.